Peran dan Hakikat Kurikulum dalam Meningkatkan Efektivitas Pembelajaran - Alifah Nur Hasanah; Merysa Puspita Dewi; Risa Putri Aprianti; Zakia Valerina; Sofyan Iskandar (STAI AL-AMIN, 2025)
This study aims to describe the role and nature of the curriculum in improving the effectiveness of learning in an educational environment. The background of this research is based on the curriculum not only as a set of plans and arrangements regarding objectives, content, and subject matter, but also as the main guideline in the implementation of the teaching and learning process. In this context, the curriculum plays an important role in determining the direction, strategies and approaches used by teachers to achieve optimal learning objectives. This research uses a qualitative approach with a literature research method. The results show that the effectiveness of learning is highly dependent on the extent to which the curriculum is able to be applied flexibly and relevantly in accordance with the dynamics of education and the times.